Taking back control of the welfare state: Brexit, rational-imaginaries and welfare chauvinism. Issue 1 (2nd January 2022) - Donoghue, Matthew; Kuisma, Mikko
Abstract: Brexit is about more than the UK exiting the EU. For the Conservative Party, it is about reacting to the challenge from the radical right, both in terms of the electoral threat from UKIP and a long-term internal struggle between moderate Conservatives and the more radical Eurosceptic faction within the party. We ask to what extent Brexit could also be considered as the mobilisation of specific welfare chauvinist discourses and practices. Through a combination of Qualitative Content Analysis (QCA) and Critical Discourse Analysis (CDA) of key speeches and documents from the official Leave campaign, we demonstrate that, rather than merely reinforcing deservingness along ethno-national lines, Brexit invokes social citizenship to delegitimize EU institutions. The referendum result catalyses a longer-term redrawing of the boundaries of social citizenship, and the ideas of membership that grants access to services and benefits. Brexit is discursively framed to mobilise people to consent to this redrawing of boundaries.